Accelerating the Change to Smart Societies- a Strategic Knowledge-Based Framework for Smart Energy Transition of Urban Communities - Zaidan, Esmat; Ghofrani, Ali; Abulibdeh, Ammar; Jafari, Mohsen (Frontiers in Energy Research, 2022)
Urban communities differ in their social, economic, and environmental characteristics, as well as in the approach to energy use. Dynamic energy use and available on-site resources allow interaction with the surroundings and contribute to the key performance indicators of smart cities. This study aimed at proposing systematically a strategic framework for smart cities development by gradually transforming urban communities into smart-energy systems. This framework is based on multidisciplinary practices regarding the staged planning of smart communities and develops smart transformation concepts to enhance capacities toward the preservation, revitalization, livability, and sustainability of a community. In this study, we focused on the concept of smart and zero-carbon communities by using technology and infrastructure. We also considered the premise of the “community” and the related social, technological, and economic aspects. The decision constructs are explained from the perspective of a bottom-up approach ranging from preliminary inspections to economic investment planning. The study proposed a set of decision constructs aimed at allowing planners, engineers, and investors to have different alternatives at their disposal and select a feasible set of practical solutions for smart transformations accordingly.